NK-92 cells activated by IL-2 inhibit the progression of endometriosis in vitro - Jun Yao; Li-jiao Zhang; Zhe Zhou; Mao-fang Hua (Taylor & Francis Group, 2024)
Background Interleukin (IL)-2 is a key cytokine capable of modulating the immune response by activating natural killer (NK) cells. This study was recruited to explore the therapeutic potential of IL-2-activated NK-92 cells in endometriosis in vitro.Methods Ectopic endometrial stromal cells (EESCs) were isolated and co-cultured with IL-2-activated NK-92 cells at varying effector-to-target (E:T) ratios (1:0 [Control], 1:1, 1:3, and 1:9). The viability, cytotoxicity, and cell surface antigen expression of IL-2-activated NK-92 cells were assessed. The viability, apoptosis, invasion, and migration ability of EESCs co-cultured with NK-92 cells at different ratios were evaluated. The apoptosis-related proteins, invasion and migration-related proteins as well as MEK/ERK pathway were examined via western blot. Each experiment was repeated three times.Results IL-2 activation enhanced NK-92 cytotoxicity in a concentration-dependent manner. Co-culturing EESCs with IL-2-activated NK-92 cells at E:T ratios of 1:1, 1:3, and 1:9 reduced EESC viability by 20%, 45%, and 70%, respectively, compared to the control group. Apoptosis rates in EESCs increased in correlation with the NK-92 cell proportion, with the highest rate observed at a 1:9 ratio. Moreover, EESC invasion and migration were significantly inhibited by IL-2-activated NK-92 cells, with a 60% reduction in invasion and a 50% decrease in migration at the 1:9 ratio. Besides, the MEK/ERK signalling pathway was down-regulated in EESCs by IL-2-activated NK-92 cells.Conclusion IL-2-activated NK-92 cells exhibit potent cytotoxic effects against EESCs. They promote EESC apoptosis and inhibit viability, invasion, and migration through modulating the MEK/ERK signalling pathway.